Acanthopanax senticosus improves cognitive impairment in Alzheimer’s disease by promoting the phosphorylation of the MAPK signaling pathway - Zhang, Zhichun; Wu, Yonghui; Shi, Dan; Jiang, Chanyu; Cao, Hengyan; Jiang, Fengyi; Bao, Xiaomin; Shen, Yan; Shi, Xiao (Frontiers in Immunology, 2024)
Background: Acanthopanax senticosus (AS) can improve sleep, enhance memory and reduce fatigue, and is considered as an effective drug for Alzheimer's disease (AD). The therapeutic effect and mechanism need to be further investigated.To confirm AS play efficacy in alleviating memory impairment in mice, the 5×FAD transgenic mice were subjected to the open field experiment and novelty recognition experiment. Network pharmacology technique was used to analyze the information of key compounds and potential key targets of AS for the treatment of AD, molecular docking technique was applied to predict the binding ability of targets and compounds, and GO and KEGG analysis were also performed on the targets to derive properties of AS play an important role in the alleviation anxiety and memory impairment caused by AD, and the mechanism is involved in the phosphorylation and activation of the MAPK signaling pathway. The results of this study could provide a novel perspective for the clinical treatment of AD.